Reaktualisasi Pemikiran Filsafat Ibnu Sina dalam Pendidikan Islam Era Kontemporer - Naziah Nofriana (CV. Creative Tugu Pena, 2025)
This study investigates the contemporary relevance of Ibn Sina’s philosophical thought within Islamic education, focusing on his epistemological, ethical, and ontological perspectives. Through a literature-based qualitative approach, the research analyzes Ibn Sina’s educational concepts and their potential to address enduring challenges in the current Islamic education system. The findings reveal that his integrative approach combining religious and rational sciences offers a compelling solution to the long-standing dichotomy between traditional and modern knowledge paradigms. Moreover, his emphasis on ethical education and character formation underscores the importance of moral development alongside intellectual growth. Despite obstacles such as ideological resistance, limited institutional resources, and the gap between classical and modern contexts, the study identifies promising opportunities for curriculum reform through interdisciplinary approaches and technological integration. This study contributes to the discourse on Islamic educational reform by presenting Ibn Sina’s philosophical framework as a strategic model for developing a more holistic, adaptive, and future-oriented system. It highlights how classical Islamic thought can be reactualized to enhance the intellectual, moral, and practical dimensions of education in the modern era, thus bridging tradition with contemporary pedagogical needs.